The Potential for Developing Eco-Tourism in the Yagirala Forest Reserve to Maintain its Sustainability - Ruzaik, Fareena (My University, 2009)
The Yagirala Forest Reserve (YFR) has as long a history as the Sinharaja Natural Forest. It is situated in the South West lowland hills and, floristically, the richest region of the wet zone of the island. The YFR is one of the natural forests, which appears to be a “true tropical rain forest”. It has an area of approximately 2004.90 ha with an average annual rainfall of 4000 mm and temperature range of 27.0° C to 28.5° C. It is administered and managed by the Department of Forestry (DOF) and an area of 40 ha block was given to the Department of Forestry and Environmental Science (DFES) of the University of Sri Jayewardenepura (USJ) for the purpose of research and education in the year 1991. The study revealed the Yagirala Aranya Forest Reserve to be an eco-tourism destination in the Kaluthara district. Eco-tourism is nature based tourism that sustains the physical and social environment and is managed in an ecologically sustainable manner. Therefore, it is different from ordinary tourism. It minimizes the environmental impact of tourism and also brings benefits to both the local communities and the physical environment. Eco-tourism plays an important role, generating alternative income for people who depend on the forest. It reduces direct dependency and provides direct incentives to protect the forests. In addition, eco-tourism is important in product diversification and new product development, which were identified as product development strategies by the Tourism Sector Master Plan of Sri Lanka in 1995. Therefore, it is preferable that all tourism should become eco-tourism. Considering the above, the study was designed with the main objectives of identifying the potential of the YFR to develop eco-tourism and to design an appropriate plan to enhance its economic value towards the benefit of livelihood. Primary data was collected through field study. Field work includes tree mensuration, observations and discussions. The observation and discussion concentrated on identifying the potential of the YFR. Secondary data was also used for this study. The result obtained from the study revealed that the YFR has rich biodiversity, natural scenic beauty and easy accessibility, which are vital elements to promote 2 eco-tourism. The YFR, a biological hotspot and a protected area, is no exception. It is unique and exceptional in its own way as it is the only forest reserve in the world where two varieties of fish, the red neck goby, and the lipstick goby are found. Apart from the unique species of fish, the YFR has over a hundred different species of animals, many of them endemic to the island. Approximately, 36 species of mammals and 62 flora families are available in the YFR. Further, the YFR contains many places with religious, cultural, historical and environmental values which offer opportunities for climbing, walking, bird watching, swimming etc. Accordingly, the study revealed the necessity of preparing an effective Sustainable Management Plan for promoting eco-tourism in the YFR with the collaboration of related institutions.